Effect of chlorination on barnacle larval stages: Implications for biofouling control and environmental impact. (April 2016) - Venkatnarayanan, Srinivas; Murthy, P. Sriyutha; Kirubagaran, Ramalingam; Venugopalan, Vayalam P.
Abstract: Continuous low-dose chlorination (CLDC, 0.2 ± 0.1 mg l −1 ) is practised to control mussel settlement in industrial cooling systems. However, its effect on larval barnacles is poorly understood. Experiments were carried out with larvae of the barnacle Amphibalanus reticulatus to assess: 1) chlorine toxicity to discrete naupliar stages, 2) effect of transient chlorine exposure of nauplii on subsequent larval development and 3) effect of chlorine on cypris settlement and metamorphosis. Individual naupliar stages showed different levels of sensitivity to chlorine exposures with the stage II nauplii being the most susceptible to in-use levels (0.2 ± 0.1 mg l −1 ) of chlorination. Short term exposures (3–20 min) to 0.2 mg l −1 chlorine did not prevent larval settlement. A significant percentage of treated cyprid larvae (non-feeding stage) survived, settled and metamorphosed to juveniles. A fraction of the chlorine-treated cypris larvae precociously metamorphosed into juveniles, bypassing cementation to substratum. About half of the pre-competent larvae (naupliar stages) exposed to in-use levels of chlorine failed to reach cypris stage, indicating that CLDC can impact barnacle larval development in the sea. In barnacle dominated systems, use of alternative control strategies/biocides may be required. Highlights: The effect of chlorination on competent (cypris) and pre-competent (nauplius) larvae was studied. Continuous low dose chlorination has limited effect on cypris survival and settlement. Larval development in nauplii is affected.